Fabrication and characterization of laser-ablated cladding resonances of two different-diameter photosensitive optical fibers - Islam, M.R.; Gunawardena, D.S.; Lee, Y.S.; Lim, Kok Sing; Yang, H.Z.; Ahmad, Harith (Elsevier, 2016)
In this work, we demonstrate the inscription of grating in both cladding and core of photosensitive single-mode optical fibers with diameter 4.4/125 μm and 4.2/80 μm. Such inscription is made possible through a hydrogenation process for the photosensitive fiber and employ high energy focused pulsed laser from an ArF excimer laser. In the fabrication, a periodic ablation is formed on the fiber surface and the optical damage is extended from the fiber surface towards the core of the fiber, observable under an optical microscope. As a result, cladding modes are excited and cladding resonances are produced in the output spectra. The response of cladding resonances to ambient refractive index (RI) is characterized and investigated through simulation and experiment. It is observed that cladding resonances in the fiber with smaller diameter are more sensitive to the ambient RI variation.